1ISG-008 Flat doses of anti-PD1: what is the economic impact?. (March 2019) - Meurant, A; Michel, G; Morin-Légier, V; Delplanque, R
Abstract : Background: In 2018 the European Summary of Product Characteristics (SPC) of Opdivo (nivolumab) and Keytruda (pembrolizumab) used in monotherapy were modified. The weight-based doses were replaced by flat doses. Purpose: We studied the economic impact of these changes in posology at the level of our hospital. Material and methods: The data: indications, weight and doses prescribed were extracted from our chemotherapies' prescription and preparation database software. We selected patients treated by Opdivo for a melanoma or a non-small cell lung cancer (NSCLC) and those treated by Keytruda for a melanoma. The patients selected were currently treated with a weight-based dose, then with a flat dose after modification of the SPC. For each patient the economic impact associated with the change of dose was quantified. Results: Twenty-eight patients treated by Opdivo were analysed. Before modification of the SPC the average dose prescribed was 233 mg (147 mg; 375 mg). An increase in dose was observed for 18 patients (64%) and a decrease in dose was observed for 10 patients (36%). The average additional cost per cure per patient with aflat dose was €73 (€10.6/mg of Opdivo) and the estimated additional annual cost for our hospital is €53 319. Six patients treated by Keytruda were analysed. Before modification of the SPC the average dose prescribed was 175.4 mg (138 mg; 200 mg). An increase in dose was observed for five patients (80%), and the dose was maintained for one patient (20%). The average additional cost per cure per patient with a flat dose was €647€ (€26.3/mg of Keytruda) and the estimated additional annual cost for our hospital is €67 445. Conclusion: The flat doses now recommended increase on average the anti-PD1 dose administered to the patients. This generates an additional estimated cost for the hospital of about €1 20 000 a year. The toxicity data with superior doses are reassuring, but no clinical benefit is demonstrated. Benefits on the safety side and on the organisation side with flat doses appear debatable in view of the derived additional costs. This approach could be applied to the posology of Keytruda as first line of the NSCLC. A weight-based dose would decrease the cost by €3 78 000 per year for our hospital, with 11 patients currently treated. References and/or acknowledgements: No conflict of interest.